Psychometric properties and validation of two global impression questionnaires (PGI‐S, PGI‐I) for stress incontinence in a German‐speaking female population. Issue 4 (11th November 2017) - Bjelic‐Radisic, Vesna; Ulrich, Daniela; Hinterholzer, Susanne; Reinstadler, Evi; Geiss, Ingrid; Aigmueller, Thomas; Tamussino, Karl; Greimel, Elfriede; Trutnovsky, Gerda; ,
Abstract : Aims: The Patient Global Index of Severity (PGI‐S) and the Patient Global Index of Improvement (PGI‐I) are global impression questionnaires developed in English and validated in women with stress urinary incontinence (SUI). This validation study tested the psychometric properties of German‐language versions of the two questionnaires in German‐speaking women with SUI. Methods: The German‐language PGI‐S and PGI‐I were psychometrically tested and validated using the SF‐12 questionnaire, the Kinǵs Health Questionnaire (KHQ), clinical parameters, incontinence episode frequency and pad use in 311 patients before and 3 months after receiving a TVT‐O or TVT tape for SUI. Results: At baseline and 3 months postoperatively there was a positive correlation between PGI‐S response categories and clinical parameters, IEF and pad use, and nearly all KHQ subscales. There were no correlations between response categories of PGI‐S at baseline and PGI‐I at 3 months and the SF‐12 scales PCS‐12 and MCS‐12. Conclusion: Our results demonstrated good psychometric properties of the German‐language PGI‐S and PGI in German‐speaking women with SUI.